(untitled) (Revista Argentina de Cirugía, 2026)
Background: The treatment of advanced gastric cancer involves a radical gastrectomy and adequate lymphadenectomy. The results of laparoscopic surgery are similar to those of open surgery. Objective: The aim of this study was to gather information from centers performing laparoscopic D2 gastrectomy (LD2G) procedures in Argentina and to compare the morbidity, mortality and oncological outcomes in high- versus low-volume centers. Materials and methods: We conducted a national survey of centers performing LD2G procedures and recorded morbidity, mortality, and pathological findings. The sample was divided into two groups according to the number of LD2G procedures performed annually: those performing ≥ 20 and <20. Results: Seventeen centers responded the survey of which 4 (23.6%) perform ≥ 20 LD2G procedures. The mean number of procedures per year was 6.5 in group < 20, and 30 in group ≥ 20. In group < 20, mean operative time was 220 minutes, conversion rate was 8.3%, the mean number of lymph nodes dissected was 18.4, and the percentage of clear margins was 92.1%. In group ≥20, mean operative time was 290 minutes, conversion rate was 8.6%, the mean number of lymph nodes dissected was 30.5, and the percentage of clear margins was 93.1%. Major complications occurred in 11.8% of the cases in group <20 and in 17.3% in group ≥20. Mortality rates were 4.6% and 2.7%, respectively. Conclusions: The medical centers performing ≥20 LD2G procedures per year demonstrate enhanced oncological outcomes and lower mortality with a morbidity rate similar to the one reported in the literature.